Water Availability in the Moayat River in Meeting Water Needs in Kotamobagu, North Sulawesi - Mokodongan, Masita Aisza; Kurniyaningrum, Endah; Yuwono, Bambang Endro; Pontan, Darmawan (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2025)
The Moayat River in Kotamobagu, North Sulawesi, plays an important roleas a water source to meet the needs of the local community. However, water management in this area faces significant challenges due to seasonal discharge fluctuations, changes in land cover, and increasing water demand. This study aims to analyze the water availability of the Moayat River based on surface water conditions and current water demand assessments, future water demand projections, and water balance evaluations. The results show that current water availability is sufficient to meet domestic water needs. However, surface water conditions are influenced by climate change indicators, so that river discharge approaches the water demand threshold, thus creating a risk of water shortages,especially for irrigation. Over the past decade, forest cover in the catchment area has decreased, which has led to increased surface runoff and reduced water infiltration. Based on these findings, climate change in land cover greatly affects surface flow conditions so that an integrated management strategy is needed, including watershed rehabilitation, development of water storage infrastructure, and increasing water use efficiency, is essential to ensure the long-term sustainability of water supply from the Moayat River.